The Impact of Emigration on the Competitiveness of the Country: the Case of Lithuania - Rita Remeikiene; Ligita Gaspareniene (Institute of Economic Research (IER), 2017)
Increasing flows of migration have not only positive, but also negative effects on economics, first of all, by causing substantial disproportions in the labour market. Lithuanian national economy has been hurt by excessive emigration rates. With reference to the projections of 'Eurostat' (2015, pp. 1-16), by 2060, Lithuanian population will have decreased by 1.8 million. Loss of such big quantities of the labour force is dramatically reducing competitiveness of the country. Although scientific literature is relatively rich in the studies on the links between emigration and general structural components of competitiveness, the current and plausible future impact of high emigration rates on the competitiveness of Lithuania has hardly been researched. To assess the impact of emigration on the competitiveness of Lithuanian economics. Comparative and systematic analysis of the scientific literature, correlation analysis. It has been found that a substantial part of the indicators of Lithuanian competitiveness show different trends than those which are described in the scientific literature. This finding discloses the complexity of the situation in the country. It should be noted that although the country is losing its labour force, the rates of GDP per capita are increasing. This tendency can be explained by intensive flows of investment in R&D, i.e. the model of the country's economy is being redirected from cheap labour to technology-based economy. Nevertheless, the situation in the country is worsened by sustainability of high unemployment rate and high risk of population's poverty. Lithuania really needs to start caring about its demographic resources because in the future the trends of low birthrate and aging society will ultimately cause the problems of social support and tax burden for the employed population.
Keywords: J11; O15; 330; export; factors; evaluation; Lithuania